ISOLATION AND IDENTIFICATION OF ENTEROBACTER SPP. IN DOG DIARRHEA - Krisnawati, Matilda; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2022)
This study aims to isolate and identify Enterobacter spp. from the digestive tract of dogs with diarrhea. Diarrhea is a digestive disease that commonly attacks dogs, one of which can be caused by Enterobacter spp. This study using 48 samples in the form of a dog with diarrhea rectal swabs from Denpasar and surrounding areas. The samples were isolated on Eosin Methylene Blue Agar, MacConkey, and Blood Agar media by streak method and then incubated for 24 hours at 37°C, then primary tests were carried out, namely gram staining, catalase test, and oxidase test, and identification tests were carried out on Triple media. Sugar Iron Agar, Simon Citrate Agar, Sulfide Indole Motility, Methyl Red Voges Proskauer, and sugar test. The results showed that two (4.16%) positive samples of Enterobacter spp. diarrhea in dogs. Therefore it can be concluded that Enterobacter spp. can be isolated and identified in the digestive tract of dogs with diarrhea. Howewer, it is necessary to carry out identification test for each Enterobacter species and more in-depth research on the pathogenicity of Enterobacter spp.